2015
DOI: 10.1016/j.heares.2015.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Speech quality evaluation of a sparse coding shrinkage noise reduction algorithm with normal hearing and hearing impaired listeners

Abstract: Please cite this article as: Sang, J., Hu, H., Zheng, C., Li, G., Lutman, M.E, Bleeck, S., Speech quality evaluation of a sparse coding shrinkage noise reduction algorithm with normal hearing and hearing impaired listeners, Hearing Research (2015Research ( ), doi: 10.1016Research ( /j.heares.2015 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The recognition ability of NH and hearing-impaired (HI) listeners 10 is increased using the "auditory masked threshold noise suppression" technique 10 under noisy conditions. 11 Conversely, babble noise for HI listeners, 12 speech-shaped quality and speech intelligibility in speech-shaped noise were improved using the laboratory-tested sparse code shrinkage algorithm. Past works have reported that using single-channel enhancement algorithms for HI listeners has shown poor performance in word recognition but not for listener preference.…”
Section: Introductionmentioning
confidence: 99%
“…The recognition ability of NH and hearing-impaired (HI) listeners 10 is increased using the "auditory masked threshold noise suppression" technique 10 under noisy conditions. 11 Conversely, babble noise for HI listeners, 12 speech-shaped quality and speech intelligibility in speech-shaped noise were improved using the laboratory-tested sparse code shrinkage algorithm. Past works have reported that using single-channel enhancement algorithms for HI listeners has shown poor performance in word recognition but not for listener preference.…”
Section: Introductionmentioning
confidence: 99%
“…At frequencies of 2.0–8.0 kHz (especially 3.0–4.5 kHz), the human ear has a higher sensitivity (the Fletcher–Munson curves of equal volume levels ISO 226: 2003), and sounds are perceived as being 10–20 dB louder than those outside this range, at same intensity [21]. Furthermore, in this frequency range, essential parts of speech information are located [22], impeding communication within the OT team. Persistent, high levels of noise are known to lead to health problems [23–26].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing sound level more than 12 dB over the background noise does not affect significant increase in speech quality 26. Despite optimal volume and frequency transmission, speech quality and definition decreases with increased reverberation times.…”
Section: Discussionmentioning
confidence: 87%